Theoretical modeling of temperature pulsations in plant leaf which are caused by leaf swing with respect to The Sun - Sirvydas, Algimantas Povilas; Kucinskas, Vidmantas; Kerpauskas, Paulius; Nadzeikienė, Juratė (Journal of Environmental Engineering and Landscape Management, 2011)
The plant leaf temperature is a result of biological processes occurring in an organ of the plant and its energy exchange with the environment. The plant leaf temperature always differs from the ambient temperature except for the moments of transition from a positive to a negative (or vice versa) temperature gradient. It is determined that the plant leaf temperature continuously changes during the sunny time of the day. Temperature pulsations emerge in plant tissues when the leaf naturally changes its position with respect to the Sun (e.g. impacted by the wind) during the sunny period of the day. When a leaf position changes with respect to the source of radiation, a temperature change in the plant leaf also depends on local plant leaf thickness δ, leaf position angle β, leaf oscillation frequency ƒ and a temperature difference between the leaf surface and the atmosphere. When changing its position with respect to the Sun during the sunny period of the day the plant leaf plate becomes a temperature mosaic. Changing the leaf tillt angle from 30° to 60° depending on leaf thickness δ, it is estimated by mathematical modeling that during 6 s the temperature change in the plant leaf reaches 0,03-0,29° C (when β=30°) and 0,11-1,04°C (when β=60°) respectively. Temperature pulsations in the plant leaf entail local temperature gradients in the leaf plate as well as changes in the local balance of plant leaf energies. The anatomic framework of the plant leaf predetermines different local impulses of temperature changes in the plant leaf. The emerged temperature gradient generates heat fluxes in the plant leaf plate.Article in English.Lokalių augalo temperatūros pulsacijų, kurias sukelia lapo svyravimai Saulės atžvilgiu, teorinis modeliavimasSantrauka. Augalo organo temperatūra yra augalo organe vykstančių biologinių procesų ir jo energinės apykaitos su aplinka rezultatas. Augalo lapo temperatūra, išskyrus perėjimo momentus iš teigiamo į neigiamą (arba atvirkščiai) temperatūros gradientą, visuomet skiriasi nuo aplinkos temperatūros. Nustatyta, kad saulėtu paros metu augalo lapo temperatūra nuolat kinta. Saulėtu paros metu natūraliai keičiantis augalo lapo padėčiai Saulės atžvilgiu (pvz., dėl vėjo poveikio) lapo audiniuose kyla temperatūros pulsacijos. Temperatūros pokytis augalo lape, kintant lapo padėčiai spinduliavimo Šaltinio atžvilgiu, priklauso ir nuo lokalaus augalo lapo storio δ, lapo padėties kampo β, lapo svyravimo dažnio ƒ ir temperatūrų skirtumo tarp lapo paviršiaus ir aplinkos. Augalo lapo plokštelė, saulėtu paros metu keisdama padėtį Saulės atžvilgiu, tampa temperatūrine mozaika. Kintant lapo posvyrio kampui nuo 30° iki 60°, matematiškai modeliuojant nustatyta, per 6 s temperatūros pokytis augalo lape priklausomai nuo lapo storio δ (0,11 mm) atitinkamai siekia 0,03-0,29° C (kai β=30°) ir 0,11-1,04° C (kai β=60°). Dėl temperatūros pulsacijų augalo lape susidaro lokalieji temperatūros gradientai lapo plokštelėje, atsiranda pokyčių lokaliame augalo lapo energijų balanse. Dėl augalo lapo anatominės sandaros augalo lape susidaro lokalūs temperatuūros pokyčio impulsai. temperatūros gradientas augalo lapo plokštelėje sukuria šilumos srautus.Reikšminiai žodžiai: augalo lapo temperatūra, temperatūros pulsacijos, temperatūros gradientas, energijų balansas.Теоретическое моделирование локальных пульсаций температуры,вызываемых колебанием листa растения относительно CолнцаРезюме. Температура органа растения является результатом биологических процессов в нем и его энергетического обменас окружающей средой. Температура листа растения, за исключением моментов перехода от положительного котрицательному (или наоборот) градиенту температуры, всегда отличается от температуры окружающей среды.Установлено, что в солнечные часы дня при натуральном изменении положения листа по отношению к Солнцутемпература листа постоянно меняется. В солнечные часы дня при натуральном изменении положения листаотносительно Солнца (например, под влиянием ветра) в тканях листа возникают температурные пульсации.Температурные изменения в листе растения зависят от локальной толщины листа δ, угла положения листа β,частоты колебаний листа f и разницы между температурой листа и окружающей среды. В солнечные часы дняпластинка листа растения под влиянием ветра меняет положение относительно Солнца и становитсяпульсирующей температурной мозаикой. Математическим моделированием установлено, что изменение угла положения листа β от 30° до 60° в зависимости от толщины листа δ (0,1–1 мм) в течение 6 с вызывает температурные изменения соответственно 0,03–0,29 °C (при β = 30°) и 0,11–1,04°C (при β = 60°). Пульсации температуры влисте растения вызывают локальные градиенты температуры, а также изменения в локальном энергетическомбалансе листа растения. Анатомическая структура листа растения является причиной, вызывающей локальныеизменения температуры, что создает тепловые потоки в пластинке листа растения под влиянием температурногоградиента.Ключевые слова: температура листа растения, температурные пульсации, температурный градиент, энергетический баланс.